Immediate versus delayed feedback effects on mathematics achievement - Ogena, Ester B., 1956- (1977)
This study compared two third year mathematics classes who were given immediate and delayed feedback on students' examination papers to determine which had better achievement results and which was more efficient of the two types in terms of the student scores, and how the two treatment groups differ in terms of score range from achievement to retention test. Two groups of 40 students were assigned to either of the two treatments. Formative tests, an achievement test, and a retention test were administered to both groups. The t-test was used for comparison of the two groups. It was revealed that immediate and delayed feedback were equally good for formative tests. For achievement and retention tests of both sexes, immediate feedback is superior than delayed feedback. Both feedback are equally good in bringing about significant change in exam scores.
December, 1977.
Thesis (M.A.T. Secondary Mathematics)--University of the Philippines, Diliman.
Keywords: Mathematical ability -- Testing; Academic achievement -- Philippines -- Testing; Geometry -- Study and teaching (Secondary) -- Philippines; High school sltudents -- Philippines